(untitled) (Nigerian Journal of Physiological Sciences, 2019)
The World Health Organization (WHO) estimates that, about a quarter of the diseases facing mankind today occur due to prolonged exposure to environmental pollution, and that most of these environment-related diseases are however, not easily detected and may be acquired during childhood and manifested later in adulthood. The aim of this work was to evaluate sub-chronic effects of lead poisoning on haematological parameters and some sex hormones, as well as age-related changes on Wistar Rats. Thirty (30) of 3-, 5-, and 7-months old male Wistar rats, were divided into experimental (lead fed) and control (distil water) groups. Haematological parameters were determined, while blood lead concentration was determined using the method of Atomic Absorption Spectrophotometer. There was a significant (P< 0.05) increase (46.00, 46.75, 50.75 vs 14.56, 18.00, 17.60) in blood lead concentration with insignificant (P˃ 0.05) increase in the concentration of WBC counts (12.433, 13.000, 12.250 Vs 12.400, 10.000, 11.250) between the experimental and control groups. Significant decrease in Body Weight (77.43, 107.88, 134.35Vs 130.66, 150.60, 165.62), RBC counts (5.333, 7.000, 6.250 Vs 7.000, 7.500, 7.250), PCV (22.667, 40.00, 35.25 Vs 37.600, 45.5,43.25), Hb (10.000, 12.000, 10.75 Vs 13.200, 13.250, 12.50), MCV (45.333, 54.500, 55.750 Vs 55.400, 59.500, 58.250), MCH levels (15.00016.25016.500 Vs 18.400, 17.750, 17.000), as well as insignificant decrease in platelet counts(410, 373, 341 Vs 437, 313, 384), and MCHC (29.67, 29.75, 30.00 Vs 32.800, 30.25, 29.250). The effect of lead (Pb) on these parameters was observed to be more pronounced in younger animals (P≤0.05). It was concluded that, ingestion of lead acetate produces more physiological derangement in young Wistar Rats.